The position of images – Text, photography and cinema. Didi-Huberman on Benjamin, Brecht and Pasolini - Mello, Marcelo Cordeiro de (Linha D’Água, 2022)
In this article we examine the interchange between playwright Bertolt Brecht and filmmaker Pier Paolo Pasolini according to the interpretation of philosopher and art historian Georges Didi-Huberman. Our analysis draws on several studies by Didi-Huberman on each of these two artists: in the case of Brecht, the long essay When Images Take Positions analyzes Brecht’s works that mix text and photography. We attempt to draw parallels between this essay and Didi-Huberman’s analysis in two conferences, of Pasolini’s La rabbia, a poetic documentary. More broadly, in our article, we explore various concepts of Didi-Huberman's thought on the relationship between text and image, and on the repositioning and permutations between images (especially historical images), and attempt to connect Didi-Huberman's work with the works of Brecht and Pasolini. We use Didi-Huberman’s concepts such as montage, survival and dissimilarity, among others.